UMAT ISLAM ANTARA IDELITAS DAN REALITAS - Musrin Musrin (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Islam as a religion of Allah includes teachings whose primary purpose is the conduct of human life in a condition that is safe, secure peace, prosperity, and quality. Such conditions will only be achieved if the values of Islamic teachings that come from al-Qur'an al-Sunnah and used as guidelines by the adherents both in attitude and behavior,'' I left you two things that if you cling to them, must be forever will not slip (that) al-Quran and al-Sunnah.''